Memória e trabalho: a inserção socioprodutiva do sujeito da hortelã na microrregião de Toledo/PR: 1959 1980. - Voll, Francisco André Pedersen (2015)
This research sought to understand the socio-productive insertion of work fronts in the micro region of Toledo by the mint plantations. This research tried to comprehend the inclusion of mint in the analyzed space, who composed the social group dedicated to mint activity and what were the results of this activity to the micro region. Interviews with people who were directly linked to the production of mint and essential oil were held in addition to the obtainment of other documents, such as photographs and production data. It was found that within the mint production different working relationships were developed, which also established different social relations between the subjects. It was also observed that the subjects directly involved in the mint activity managed to build their living spaces among other groups also established in the micro region of Toledo. Finally, it was observed that the end of the mint production on this micro-region brought significant changes, which mainly affected the municipalities with highest productions.